International symposium 'One year after the Sabra and Shatilla Massacre' (International Secretariat in Solidarity with the Arab People and Their Central Cause 'Palestine', 1983)
Black and white lithograph depicting a person in agony Poster advertising symposium on the Sabra and Shatila massacre, held in Athens, September, 1983 PO-1327